2017
DOI: 10.1002/cyto.b.21604
|View full text |Cite
|
Sign up to set email alerts
|

Normal variation of bone marrow B‐cell precursors according to age – reference ranges for studies in myelodysplastic syndromes in Brazil

Abstract: in normal individuals, BM B-cell precursors varied mainly according to age, but were also dependent on technical peculiarities of operators and equipments. Analysis by phenotype and as percentage of total nucleated cells was more accurate and less susceptible to variation than evaluating % BCPs/total CD34 cells. © 2017 International Clinical Cytometry Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 31 publications
1
15
0
2
Order By: Relevance
“…Concerning B-cell progenitors (hematogones type I), using the same strategy we found that patients with hematogones within the upper quartile had a better survival. This value corresponded to the normal range for age in our population, as previously demonstrated in a Brazilian multicenter study 20 . Similar results had been described by other studies concerning MDS 28 , 29 and ALL in remission after induction 30 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Concerning B-cell progenitors (hematogones type I), using the same strategy we found that patients with hematogones within the upper quartile had a better survival. This value corresponded to the normal range for age in our population, as previously demonstrated in a Brazilian multicenter study 20 . Similar results had been described by other studies concerning MDS 28 , 29 and ALL in remission after induction 30 .…”
Section: Discussionsupporting
confidence: 90%
“…Values for myeloid CD34 + cells were considered normal when below 2% 6 . For hematogones (H1), the normal Brazilian reference values for age were used 20 .…”
Section: Methods and Development Of The Scorementioning
confidence: 99%
“…However, after the completion of the induction chemotherapy, the hematopoietic recovery ability was better in patients with higher levels of hematogones. In fact, earlier reports have also demonstrated that hematogones were rarely detected in patients with myelodysplastic syndrome or aplastic anemia 2831 . Therefore, our data consistent with previous work which suggest that the emergence of hematogones may be closely related to the active hematopoietic status.…”
Section: Discussionmentioning
confidence: 94%
“…Myelodysplastic syndromes (MDS) are deemed a stem-cell disorders characterized by dysplasia and bone marrow failure that may evolve into AML, and our journal has enjoyed recent contributions on this topic (23,24). Finally, to round out the theme of aberrant myelopoiesis in this issue is the contribution from Gardikas et al (25), related to MDS.…”
Section: Issue Highlightsmentioning
confidence: 99%